2012
DOI: 10.1021/bi300781g
|View full text |Cite
|
Sign up to set email alerts
|

7-Methylguanosine Diphosphate (m7GDP) Is Not Hydrolyzed but Strongly Bound by Decapping Scavenger (DcpS) Enzymes and Potently Inhibits Their Activity

Abstract: Decapping scavenger (DcpS) enzymes catalyze the cleavage of a residual cap structure following 3′→5′ mRNA decay. Some previous studies suggested that both m7GpppG and m7GDP were substrates for DcpS hydrolysis. Herein, we show that mononucleoside diphosphates, m7GDP (7-methylguanosine diphosphate) and m32,2,7GDP (2,2,7-trimethylguanosine diphosphate), resulting from mRNA decapping by the Dcp1/2 complex in the 5′→3′ mRNA decay, are not degraded by recombinant DcpS proteins (human, nematode and yeast). Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 35 publications
6
52
0
Order By: Relevance
“…3), which may account for why only m 7 GMP was detected as the decapping product for Nudt15 in Figure 1A. Moreover, we were unable to detect a nucleoside diphosphatase activity for DcpS, which has been reported to convert m 7 Gpp to m 7 Gp (van Dijk et al 2003) and is consistent with a more recent report that demonstrated although DcpS avidly binds m 7 Gpp, it does not hydrolyze this substrate (Wypijewska et al 2012).…”
Section: Cap Cleavage Specificity Of the Nudix Proteinssupporting
confidence: 90%
“…3), which may account for why only m 7 GMP was detected as the decapping product for Nudt15 in Figure 1A. Moreover, we were unable to detect a nucleoside diphosphatase activity for DcpS, which has been reported to convert m 7 Gpp to m 7 Gp (van Dijk et al 2003) and is consistent with a more recent report that demonstrated although DcpS avidly binds m 7 Gpp, it does not hydrolyze this substrate (Wypijewska et al 2012).…”
Section: Cap Cleavage Specificity Of the Nudix Proteinssupporting
confidence: 90%
“…In fact, m 7 GDP is converted to m 7 GMP in extracts of different cells (23). DcpS has been reported to be responsible for this reaction (23,24), but this has not been confirmed by others (12,25,26). Regardless, m 7 GMP appears to be a universal intermediate of cap degradation but probably not its final product.…”
mentioning
confidence: 95%
“…Decapping scavengers: human DcpS (HsDcpS), C. elegans DcpS (CeDcpS) and A. suum DcpS (AsDcpS) were expressed in Escherichia coli and purified as His-tagged proteins by affinity chromatography using Ni-NTA agarose under native conditions. To obtain homogeneous fractions of DcpS, recombinant enzymes were further purified by gel filtration through a Pharmacia Superdex-200 column (GE Healthcare Bioscience AB) connected to AKTA FPLC system (Pharmacia-Biotech) [14]. The concentration of cap analogs and DcpS enzymes were estimated from their molar absorption coefficients [14,22].…”
Section: Methodsmentioning
confidence: 99%
“…However, the hydrolytic activity and binding affinity have been well characterized for human and Caenorhabditis elegans DcpS, indicating that these two enzymes differ in substrate length and capacity to hydrolyze trimethyleted cap analogs [14,15]. For the specific cap recognition and efficient degradation by DcpS, the following structural features are required: (1) the positive charge at the N7 position of guanine moiety, (2) 2 0 OH and 3 0 OH groups in the ribose ring of 7-methylguanosine, (3) at least triphosphate groups in the phosphate bridge [15].…”
Section: Introductionmentioning
confidence: 99%